Schelhaas, B., Ferretti, F., Novaes, A.R. and Schmidt di Friedberg, M. (eds.): Decolonising and Internationalising Geography: Essays in the History of Contested Science - Gyuris, Ferenc (Hungarian Geographical Bulletin, 2022)
-